Chemical constituents of essential oil of the endemic zingiber species (Zingiberaceae) in Vietnam, and its activity - Nguyen Phuong, Hanh; Nguyen Sinh Khang,; Nguyen Quoc Binh, (Academia Journal of Biology, 2025)
vvv